Where do we stand?: Functional imaging in acute and chronic pulmonary embolism with state-of-the-art CT - Meyer, Mathias; Haubenreisser, Holger; Janssen, Sonja; Dösch, Christina; Meyer, Melissa; Borggrefe, Martin; Schönberg, Stefan; Henzler, Thomas (European journal of radiology, 2015)
Nowadays, CT pulmonary angiography (CTPA) is the diagnostic imaging modality of choice for acute and chronic pulmonary embolism (PE) in order to assess vascular anatomy and parenchymal morphology. Over the past decade, several prognostic CTPA markers associated with an increased risk of adverse clinical events and in-hospital mortality have been evaluated, namely cardiac chamber dimensions, obstruction scores, and visualization of iodinated contrast material in the lung parenchyma by dual-energy (DE) CTPA. This article reviews the current status and potential prognostic advantages of CTPA or DE CTPA with its recent developments for accessing right ventricular dysfunction and the assessment of first pass lung perfusion with DE CTPA in the diagnosis of acute and chronic PE.